Variation between CT scan Findings and Histological Diagnosis of Intracranial Glioma - Debnath, H; Barua, KK; Hossain, A; Hoque, MF (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2008 Jul;17(2):164-8.The abstract of this article is available on the PubMed website